A Rare Site Mandibular Condyle Osteochondroma Complicated by Fracture (Journal of Nobel Medical College, 2017)
Osteochondromas are most common benign bone tumor occurring at the metaphysealregion of long tubular bone but rarely seen at maxillofacial region with less than 100 casesof mandibular condyle osteochondromas reported in literature. This article reports a rarecase of mandibular condyle osteochondroma with associated fracture in 32 years oldfemale patient presenting with sudden onset of severe pain at right preauricular regionfollowing yawning.Journal of Nobel Medical CollegeVolume 6, Number 1, Issue 10 (January-June, 2017), page: 83-85